EVALUASI KUALITAS TERHADAP PERFORMA APLIKASI DIGITAL BANKING JENIUS BTPN MENGGUNAKAN FRAMEWORK ISO 25010 - Medina Nurul Zahra (2022)
Growth of globalization era impacts for every sector in worldwide, especially about digital transformation. The transformation makes us feel of role of technologies on our activities every day. Bank Tabungan Pensiunan Nasional (BTPN) is a company that focused on transaction processed. In 2016, BTPN released an digital banking called "Jenius". Jenius application have different from any digital bank because they have a lot of features and attractive user interface. At pandemic era, users of Jenius application increased so signification. But now, users always say about complain from any platform to Jenius because a performance of application is decreased. To know about the quality and performance Jenius application, we have to evaluate from user's experience and user's pov. Writer want makes a riset that analyzes by using instrument framework ISO 25010 with 200 respondens and processes using structural equation modelling (SEM). The result of this research shows that six of seven hypothesis have positive impact and significant towards Jenius application performance. Characteristics that impacts performance efficiency are functional suitability, compatibility, usability, reliability, security, and portability.